OSTEOPOROSIS PATOGENESIS DIAGNOSIS DAN PENANGANAN TERKINI - Kawiyana, I Ketut Sik (journal of internal medicine; Vol. 10, No. 2 Mei 2009, 2012)
Osteoporosis is a bone metabolic disease, which is characterized by decreased bone mass due to reduced bone matrix and mineral, accompanied by micro architecture derangement of the bone tissue. Hence, in this disorder the bone has the tendency to fracture due to low bone quality. Cell which responsible for bone formation is osteoblast, whereas osteoclast is responsible for bone resorption. In osteoporosis, bone turn over is abnormalwhichbone resorption is greater than bone formation. Therefore direct factors for osteoporosis are number and activity of osteoclast in resorbing bone, and they are influenced by mediators and the mediators depends on estrogen level. Number and activity of osteoclast cell are greater than number and activity of osteoblast cell in osteoporosis. This imbalance causes decreasing bone mass. The pathogenesis of osteoporosis has been discussed by showing the recent theories related to increase of osteoclast cellÕs differentiation and activity due to: estrogen hormon deficiency, cytokine factor and axial loading. Several means in diagnosing the risks for osteoporosis and itÕs current managements based on itÕs pathogenesis have been mentioned too.
Keywords: Osteoporosis, pathogenesis and management